An efficient flexible strain sensor based on anhydride-grafted styrene-butadiene-styrene triblock copolymer/carbon black: enhanced electrical conductivity, sensitivity and stability through solvent swelling. (16th November 2020) - Wu, Lanlan; Yao, Dahu; Gao, Xiping; Yu, Zhiqiang; Wang, Xiao; He, Yuxin; Zhu, Yan; Lu, Chang; Li, Keyang
Abstract: High-performance flexible strain sensors based on maleic anhydride-grafted styrene-butadiene-styrene triblock copolymer/carbon black (SBS-g-MAH/CB) composites were prepared by simple solvent swelling of SBS-g-MAH/CB composites obtained by melt blending. After swelling in N, N-dimethylformamide (DMF) or xylene, the aggregation of CB in the composites was reduced noticeably. Consequently, the conductivity of the composites improved by a great extent, and the percolation thresholds of the composites decreased. At 12% CB loading, the conductivity increased approximately 400 times or 6000 times upon swelling in DMF or xylene, respectively. DMF swelling did not change the morphology of SBS-g-MAH, and a three-dimensional conductive network was formed in the composites. The SBS-g-MAH morphology changed considerably, and a two-dimensional conductive network was formed after swelling in xylene. DMF swelling enhanced the piezoresistive performance of the composites. The gauge factor increased from 4 to 71. Moreover, the drawbacks of composites prepared by melt blending, including electromechanical inconsistency and poor stability, were overcome. Due to the high conductivity and the change in SBS-g-MAH morphology, an approximately two-fold increase in electromagnetic interference shielding efficiency was observed after swelling the composites in xylene. The mechanism of the strain sensor was discussed. The strain sensing behaviour of SBS-g-MAH/CB composites can be explained by an analytical model based on the tunneling theory.